A Novel Frequency Regulation in Islanded Microgrid using Sliding Mode Control with Disturbance Observers considering Storages and EVs. (January 2023) - Ibraheem, Mohamad Issa; Edrisi, Mehdi; Gholipour, Mehdi; Haes Alhelou, Hassan
Abstract: A variation in load on a microgrid (MG) system has a significant impact on the MG's frequency. In addition, wind and photovoltaic power sources are significantly affected by weather fluctuations; thus, the system experiences frequent oscillations. This paper proposes an integral sliding mode control system that incorporates a disturbance observer (ISMCDO) for establishing a power balance and frequency regulation in a MG system. MATLAB/ Simulink is used to compare the results of this method and those of integral sliding mode controller (ISMC) and disturbance observer-based controller (DOBC). In addition, their performance indices are compared as well, where the results can verify the superiority of ISMCDO method in comparison with other techniques. Consequently, Utilizing the ISMCDO controller, the secondary controller performances in the MG system may be improved, which will ensure stability, flexibility, quick response, and maintenance of the load balance when sudden changes in loads and weather conditions occur.